Pengaruh Alat Permainan Edukatif Papan Matematika Terhadap Kemampuan Numerasi Anak Usia 5-6 Tahun - Elsa Meriska Br siboro; Wan Nova Listia (LP3M IAI Al Urwatul Wutsqo Jombang, 2026)
This study aims to determine the effect of using educational game tools in the form The present study was conducted with a view to analysing the effect of utilising educational games (APE) such as math boards on the numeracy skills of 5-6-year- old children at Mutiara Bunda Galang Kota Kindergarten. The present study concentrated on alterations in the domain of numeracy skills, encompassing activities such as enumeration, number sequencing, the matching of number symbols with corresponding quantities, and the execution of rudimentary arithmetic operations. The present study adopted a quantitative approach, employing an experimental method through a one-group pretest–posttest design. The subjects of the research study comprised 15 children aged between 5 and 6 years old, who constituted Group B. The data was collected through the implementation of observational techniques, utilising instruments that had been meticulously compiled on the basis of indicators pertaining to numeracy ability. The Wilcoxon test was employed to analyse the data, with the objective of ascertaining the variation in numeracy abilities both prior to and following the administration of the treatment. The findings of the investigation demonstrated an enhancement in numeracy scores in the post-test phase in comparison to the pre-test phase. These findings were reinforced by the results of the hypothesis test, which demonstrated that the utilisation of the mathematical board APE exerted a significant influence on children's numeracy skills. It is evident from the findings of this study that the mathematical board educational game tool is an effective medium for enhancing the numeracy skills of 5-6-year-old children at Mutiara Bunda Galang Kota Kindergarten